The influence of leaders' implicit followership theories on employee outcomes - Kedharnath, Uma, author; Gibbons, Alyssa Anne Mitchell, committee member; Byrne, Zinta S., committee member; Henry, Kimberly, committee member; Johnson, Stefanie K., committee member; Mumford, Troy V., committee member (Colorado State University. Libraries, 2011)
This paper addressed a new concept called leader's implicit followership theories (LIFTs), which can be defined as leaders' pre-existing beliefs about followers' personal attributes and characteristics (Sy, 2010). The goal of this paper was to address the impact of LIFTs on employee outcomes. Specifically, LIFTs were hypothesized to influence the relationship between supervisors and their employees. Employees' perception of this relationship was hypothesized to influence employee outcomes - namely, employee job satisfaction and organizational commitment. This model was partially supported. Supervisor LIFTs did not predict employees' perceptions of the relationship with their supervisor. Employees' perceptions of the relationship predicted job satisfaction and organizational commitment. Conceptual and measurement limitations of LIFTs and future directions for research on LIFTs are discussed.
Keywords: job satisfaction; implicit theories; followership; leader member exchange theory; leadership; organizational commitment